Stay just a little bit longer - Kogar, Anshul (Nature physics, 2021)
The short lifetime of light-induced superconductivity prevents the measurement of its transport properties. Encouraging this state to stay a little longer in K 3 C 60 allows the observation of vanishing electrical resistance.